Plastics injection molding : scientific molding, recommendations, and best practices. - Lerma Valero, José R. (HANSER PUBLICATIONS, 2020)
Plastics Injection Molding: Scientific Molding, Recommendations, and Best Practices" is a user-friendly reference book and training tool, with all the essentials to understand injection molding of plastics. It is a practical guide to refining and controlling the process, increasing robustness and consistency, increasing productivity and profitability, and reducing costs. This book contains structured information on process definitions and parameters, optimization methods, key points, interpretation of data sheets, among other useful recommendations regarding both technology and design. It also provides analysis of process deviation, defects, incidents, etc. as well as a section dedicated to material selection and comparison. Includes a bonus of downloadable Excel spreadsheets for application to scientific molding, process analysis, and optimization. This book is aimed at injection molding technicians, process engineers, quality engineers, mold designers, part designers, simulation engineers, team leaders, plant managers, and those responsible for purchasing plastic materials